Jackson Memorial building plaque - Maskell, Harry (Tufts Archival Research Center, 2015)
8 x 10, photographic print. Plaque formerly in Jackson Memorial building, Ash street and Nassau street, commemorating the bequest from the estate of Henry Clay Jackson and Paul Wilde Jackson which enabled the Boston Floating Hospital to build this, its first land-based building.